Left Atrial Function in Patients with Chronic Chagasic Cardiomyopathy - Fragata,Claudia da Silva (2015)
Background:Chagas disease is a cause of dilated cardiomyopathy, and information about left atrial (LA) function in this disease still lacks.Objective:To assess the different LA functions (reservoir, conduit and pump functions) and their correlation with the echocardiographic parameters of left ventricular (LV) systolic and diastolic functions.Methods:10 control subjects (CG), and patients with Chagas disease as follows: 26 with the indeterminate form (GI); 30 with ECG alterations (GII); and 19 with LV dysfunction (GIII). All patients underwent M-mode and two-dimensional echocardiography, pulsed-wave Doppler and tissue Doppler imaging.Results:Reservoir function (Total Emptying Fraction: TEF): (p <0.0001), lower in GIII as compared to CG (p = 0.003), GI (p <0.001) and GII (p <0.001). Conduit function (Passive Emptying Fraction: PEF): (p = 0.004), lower in GIII (GIII and CG, p = 0.06; GI and GII, p = 0.06; and GII and GIII, p = 0.07). Pump function (Active Emptying Fraction: AEF): (p = 0.0001), lower in GIII as compared to CG (p = 0.05), GI (p<0.0001) and GII (p = 0.002). There was a negative correlation of E/e’average with the reservoir and pump functions (TEF and AEF), and a positive correlation of e’average with s’ wave (both septal and lateral walls) and the reservoir, conduit and pump LA functions.Conclusion:An impairment of LA functions in Chagas cardiomyopathy was observed.